Before I Say Goodbye: Autobiography and Closure in Alice Munro's “Finale” - Lucio-Villegas Spillard, Iris Melanie (International Journal of English Studies, 2021)
Alice Munro published in 2012 her last collection of short stories, Dear Life, which includes “Finale”, a quartet of stories introduced by the author in semiautobiographical terms. The relevance of the themes addressed is, as may be inferred, significant in relation to her life and previous work. In fact, they echo her first two collections of short stories —Dance of the Happy Shades (1968) and Lives of Girls and Women (1971)— not only in motifs and events, but also in style. This paper analyses and compares this last section —Munro’s conclusive contribution to the literary world— with her early work to establish joint features and similarities in order to support and extend the often-claimed autobiographical dimension of Munro’s fiction from this unexplored perspective. In addition, this process of analogy has recognised the author’s literary and emotional closure in relation to her mother, a hitherto elusive endeavour in her work.